Meningkatkan Hasil Belajar IPS Melalui Model Pembelajaran Think Pair Share - Tiorly Sinaga (JURNAL GLOBAL EDUKASI, 2017)
Abstract: The purpose of this research is to improve IPS learning outcomes through thinking pair share learning model. Subjects in this study were the students of class VI SD Negeri 013847 Serdang kec. Meranti TP. 2016/2017. This research is conducted to improve learning outcomes through learning model of learning Think Pair Share material role of Indonesia in globalization era of lesson IPS student grade VI SDN 013847 Serdang kec. Meranti TP. 2016/2017. The result of learning process after research through Think Pair Share learning model reaches an average value of 72.83. With the percentage of learning completeness klasikal equal to 57%. Results from cycle II obtained an average value of 84.84 with a percentage of classical learning completeness of 87%. Keyword: think pair share, globalization Abstrak: Tujuan penelitian ini adalah untuk meningkatkan hasil belajar IPS melalui model pembelajaran think pair share. Subjek dalam penelitian ini adalah siswa kelas VI SD Negeri 013847 Serdang kec. Meranti TP. 2016/2017. Penelitian ini dilakukan untuk meningkatkan hasil belajar melalui model pembelajaran pembelajaran Think Pair Share materi peran Indonesia di era globalisasi pelajaran IPS siswa kelas VI SDN 013847 Serdang kec. Meranti TP. 2016/2017. Hasil proses belajar setelah penelitian melalui model pembelajaran Think Pair Share mencapai nilai rata-rata 72,83. Dengan persentase ketuntasan belajar klasikal sebesar 57%. Hasil dari siklus II diperoleh nilai rata-rata sebesar 84,84 dengan persentase ketuntasan belajar klasikal sebesar 87%. Kata kunci: think pair share, globalisasi